Analisis penggunaan ayat dalam karangan bahasa Tamil / Kumutha A/P Rakiappan - Kumutha, Rakiappan (2012)
This study was conducted to identify the understanding level and use of the sentences in Tamil Language among the teacher trainees from the Program Persediaan Ijazah Sarjana Muda Perguruan PPISMP (2010 in take) Semester 1 in IPG Kampus Raja Melewar, Seremban, Negeri Sembilan. For this study, 50 trainees were chosen as respondents. Qualitative and quantitative methods were used to collect data. The reseach was done using descriptive statistics. Data was obtained analysis through responses of trainees in tests of various types of sentences in the Tamil Language and two essays produced by them. The set of instruments used in this study was divided into 3 sections and were prepared according to the ‘Jadual Spesifikasi Ujian’ (JSU). Section A contained 25 multiple choice items, Section B had 10 structured questions and Section C required respondents to choose sentences from an essay given to them. Besides that, respondents were also required to write two essays. The tests were marked and analyses. The scripts were analyzed based on types of sentences such as simple, compound, complex, direct and indirect speeches, question types and exclamatory sentences to identify the use of such sentences in the respondents’ essays. The research finding shows that the respondents’ understanding about the types of sentences, 6% of them were gauged at excellent level, 56% ‘good’ and 38% ‘moderate’. This indicates that the respondents still lack knowledge in writing different types of sentences in their essays. They focused mainly on 3 types of sentences: the complex, simple and compound sentences, respectively. In conclusion, the research found that the respondents have the knowledge about the various types of sentences in the Tamil Language. However, in writing, they are content with using the complex, simple and compound sentences, respectively.